Improving the clinical accuracy in patients with antiphospholipid antibodies using anti-phosphatidylserine/prothrombin and anti-beta2 glycoprotein I domain and particle-based multi-analyte technology. Issue 202 (June 2021) - Radin, Massimo; Foddai, Silvia; Cecchi, Irene; Rubini, Elena; Barinotti, Alice; Mahler, Michael; Seaman, Andrea; Ramirez, Carlos; Casas, Sìlvia; Roccatello, Dario; Sciascia, Savino
Highlights: It is unknown which aPL positive patients will develop APS clinical manifestations. aPS/PT and β2GPI- Domain 1 have been proposed to be relevant to APS and its clinical manifestations. In this study we tested 122 aPL positive patients do determine the best aPL clinical accuracy. The combination of aPS/PT and β2GPI D1 might increase the diagnostic power of aPL testing.